Vertical Distribution of Sediment in the Waters of Bengkalis Strait Bengkalis Regency, Riau Province - Dedek Susanto; Rifardi '; Elizal ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted in January 2015 with the aim to determine the characteristics of the sediment vertically in Bengkalis Strait. This research used survey method which divided into 7 stations. Sediment samples were taken by using gravity cores. Analysis of the sediment was carried by the size of the analytical method and the drying method.The results showed that sediments in the location was dominated by sand fraction, then mud and gravel fractions. The result of Sediment grain size analysis showed that Bengkalis Strait have characteristics of coarse sand, medium sand, fine sand, very fine sand, silt and medium coarse silt with sorting coefficient consists of well sorted, moderately well sorted, moderately sorted, sorted pooly and very pooly sorted. The distribution of sediment was very fine skewed, fine skewed, near symmetrical, coarse and very coarse skewed. Common sediment characteristics between the station was also seen in the cluster analysis. The results of cluster analysis showed that the sediment grouped into five groups showing clearly different in the characteristics of the sediment between the stations in this area.Keywords: Vertical Distribution, Sediment, Bengkalis Strait, characteristics